Study the relationship between Selenium , Vitamin B6 , B12 and hyperhomocysteine in patients with cardiovascular disease in Thi-Qar Governorate - SATTAR, JANNAT; Mohammed A. Auda (University of Thi-Qar Journal of Science, 2023)
Cardiovascular diseases(CVD) which include ischemic heart disease, stroke, heart failure, peripheral arterial disease, and several other cardiac and vascular illnesses, are the world's leading cause of mortality and significantly lower life expectancy. The research included measuring and evaluating Homocysteine vitamin B6 , B12 and Selenium  for cardiovascular patients. Methods: This study was conducted at Nasiriya Heart Center ,Nasiriya General Hospital and Biochemistry Laboratory in the College of science University of Thi-Qar in the period between (October ,2022 to March, 2023) . In formed oral consent was taken for patients. The study included 88  subjects , ages  between (40 – 70 ) years. The subjects were divided into two groups : Control group included (38) supposed approximately healthy subject, and Patients group included (50) patients with Heart disease. Cases excluded from subjects: Kidney diseases, Liver failure, Thyroid diseases Immunological diseases, Urinary tract infections, Acute joint diseases Pregnant women, Diabetes. Results: There was a significant increase in homocysteine concentration in the blood serum of the patients group compared to the control group.  Significant decrease in the level of vitamin B6 , B12 and Selenium in the serum of patients compared to the control group. Conclusions: The study indicated that homocysteine was elevated in cardiovascular patients, which is a risk factor for heart disease. In addition, the levels of vitamins B6, B12 and Selenium decreased against the increase in homocysteine through the negative relationship  between homocysteine and vitamins B6, B12 and Selenium.